Distribution of Assets to Children Viewed From The Perspective of The Sociology of Inheritance - Khasan Alimuddin; Ilyya Muhsin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
The pre-death inheritance distribution practice in the village of Wonokerto is a phenomenon of inheritance that adheres to Javanese customary law, prioritizing several aspects of communal benefit. However, the inheritance distribution model observed in the community of Wonokerto does not obtain legal recognition in classical Fiqh or Indonesian positive law. This article aims to describe the background aspects leading the villagers of Wonokerto to engage in the pre-death inheritance distribution of the deceased, and to comprehend this practice from the perspective of the prophetic social science theory. The method employed in this writing is field research, where data is gathered through interviews with relevant informants and supplemented with supporting documentation. The research findings conclude that the distribution of parental assets to pre-deceased children is an implementation of transcendent justice.